Gamelan Sarawak A Brief Introduction - Hasnizam, Abdul Wahid; Sinin, Hamdan; Iran Amri, Musoddiq (The International Journal of Innovative Design, Creativity and Social Sciences (IJIDeCS), 2018)
Earlier research and report by Jani (2006) and Jalal (2008), have acknowledge the existence of ‘Gamelan Sarawak’. It is unique in such a way that they have been known to exist as early as in the 1920s (Jalal, 2008). Known as the most active performing gamelan group in Sarawak particularly in Kuching-Serian area, recent research has shown the ensemble have gone through significant changes ranging from their repertoire as well as their musical instruments. This paper discussed their evolution, some of the changes and challenges in sustaining the future.